The Effect of The Use of Youtube Video Media and Conventional Pictures on The Result of Remote Kick Exercise of Extracurricular Participants in SMP Islam Al-Bisyri Semarang - Suryanta, Novan Hendra; Haryono, Haryono; Khumaedi, Muhammad (Universitas Negeri Semarang, 2018)
Education technology development is inseparable with the development of technology in general. The purpose of this study was to determine and analyze the effect of the use of audio visual video Youtube media and conventional images on the results of remote kick (long pass) exercise. This study applied a quantitative approach, the method of data collection was done by using survey with test techniques and measurement. The methods of data analysis was done by using two-way ANOVA analysis, The results showed that the first hypothesis obtained Fvalue > Ftable = 9.489 > 4.260, means that the first hypothesis stating that there is a different effect between those who participate in the football club and who are non football club on their remote kick (long passing) in the extracurricular participants of football in SMP Islam Al-Bisyri Semarang is accepted. The results showed that the second hypothesis obtained Fvalue > Ftable = 21.723 > 4.260, means that the second hypothesis stating that there is a different effect between the use of learning media (youtube and conventional pictures) on the remote kick (long passing) of those who participate in the club and who are no non club in the extracurricular participants of football in SMP Islam Al-Bisyri Semarang is accepted. Based on the results of the study, it is indicated that there is an interaction between the use of learning media (youtube and conventional picture) on students who participate in the club and who are non club on their remote kick (long passing) in the extracurricular participants of football in SMP Islam Al-Bisyri Semarang. The benefits of this study shows the importance of learning by using the audio-visual media to achieve the optimal learning.